The Lero Batsir Rite as a Learning Media for Christian Religious Education in One Roof Junior High School of Wermatang,Tanimbar Islands Regency - Srue, Olivir (Institut Agama Kristen Negeri Toraja, 2023)
Abstract: The ritual process of Lero Batsir actions carried out is a rite as a layer of society which will assume that lero batsir will directly have a mechanism which will be able to provide rain which during the dry season and will directly assume the use of being able to fertilize various types plants, but on the other hand lero batsir has the advantage of being able to directly protect all layers of society who are in one area, in this case, the village. This research used a qualitative descriptive method. The results found in this research are that PAK (Christian Religious Education) can have a role in providing a deep understanding related to the concept of nature which is the result of God's creation and work which must be interpreted as God's grace to every human being. Another thing that needs to be interpreted is that there is a sense of acknowledegment or dependence on God as the source of life. Media are all physical tools that can present messages and stimulate students to learn. The process of the Lero Batsir rite which will be carried out by all levels of society in Wermatang Village to be used as Local Culture-based PAK Learning Media, especially at One Roof Junior High School of Wermatang. Keywords: Lero Batsir Rites, PAK Learning Media, Local Wisdom